Needs Analysis For The Development Of A Manual In Palliative Care For Malaysia: An Islamic Psychospiritual Approach - Che Zarrina Sa’ari; Hasimah Chik; Sharifah Basirah Syed Muhsin; Sheriza Izwa Zainuddin; Nor Azah Abdul Aziz; Khairul Hamimah Mohammad Jodi; Che Zuhaida Saari; Abdul Salam Muhamad Shukri; Salmah Karman; Abdul Ghafar Surip (Springer, 2024)
Indexed by WOS/ Scopus